PENGARUH PEMBELAJARAN ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN KOPERASI SYARIAH - Marlikan, Muchni (Department of Management, 2011)
Sekolah Tinggi Ilmu Ekonomi Indonesia MalangE-mail : mughnimarlikanstiei@yahoo.co.idABSTRACTThis research is carried out in Sharia Cooperation. The aims is to study and analyses theinfluence of learning organization and workers' motivation on workers' performance at ShariaCooperation in Malang Raya. Unit analyses in this research are 33 Co-Operation unit which isspread over Malang Town, Malang Sub-Province, and Batu Town. Research Population are 170workers who works as employees of Moslem Law Co-Operation ( BMT). Sample size is selected byusing proportional technique or sample balance (118 workers). Data are analysis by using SEM(Structural Equation Modeling) and use the program of software of computer of data processingAMOS (Analysis Of Moment Structure) v.4.0. The Result of research indicates that 1). The LearningOrganization has an positive and significant effect to employees' performance, it is proved by thestandardized value (0,526) and p-value (0,00 2). The Work Motivation of employee have an positiveand significant effect to employees' performance too, and it is proved by the standardized value(0,391) and p-value (0,00). The research conclusion is still needed the development of co-operationscience in relation with adopting economics theory and co-operation management with the publicvision (conventional) and also Moslem Law Islam. While practical implication from this research isthe improvement of human resources as an effective strength in facing the competitiveness of MoslemLaw Co-Operation (BMT) as a whole.Keywords: learning organizational , work motivate, employees performance